Control of combined convection in a nanofluid-filled lid-driven closed space via rectangular bar in the presence of magnetic field - Hussain, Shafqat; Öztop, Hakan Fehmi; Mehmood, Khalid; Ali, Mohamed E. (Springer, 2019)
In the present study, a computational work has been done to see the heat transfer, fluid flow and temperature distribution in a lid-driven cavity due to an adiabatic rectangular bar with different dimensions and locations. The closed cavity is heated from the bottom wall and cooled from the top while, vertical walls are adiabatic and magnetic field is affected in horizontally. The governing partial differential equations are discretized via monolithic Galerkin finite element method of higher order. The resulting system of nonlinear algebraic equations are linearized at the discrete solution which have been computed utilizing the efficient geometric multigrid linear solver. The influences of various physical parameters on the flow, in specific ranges such as the nanoparticle volume fraction phi=0.04, length and location of the insulated bar, Reynolds number 1Re200, Hartmann number 0Ha100 and Richardson number, 0Ri10 are investigated. It is found that the location of the bar is a good control parameter for heat and fluid flow inside the cavity. Vertical bar position becomes more effective on heat and fluid than that of horizontal bar position, and the presence of the bar becomes insignificant for the lower values of Richardson numbers.
Keywords: Combined convection; Nanofluid; Galerkin finite element method; Rectangular bar; Lid-driven closed space; Geometric multigrid method